An alternative fixation for all mild and moderate hallux valgus cases enabling intraoperative readjustment - Mesut Uluöz; Mehmet Yiğit Gökmen; Özhan Pazarcı (Journal of Orthopaedic Surgery and Research)
Abstract Background The development of a cost-effective and easily applicable fixation method to address all components of hallux valgus (HV) surgery is of great importance to the field. This study aims to assess the clinical efficacy of an  alternative fixation method that combines the advantages aspects of commonly used distal osteotomy techniques and evaluate its level of applicability in the treatment of mild and moderate HV cases. Methods The retrospectively designed study was conducted at Adana City Training and Research Hospital, Adana, Türkiye. The inclusion criteria were as follows: having undergone distal metatarsal osteotomy, minimum duration of follow-up of twelve months, and the availability of dorsoplantar weight-bearing X-ray images of the foot performed preoperatively and at the follow-up visits. The analysis data included age, gender, Visual Analog Scale (VAS) and American Orthopaedic Foot and Ankle Society (AOFAS) scores, the values of the length of the 1st metatarsal, hallux valgus angle (HVA), intermetatarsal angle (IMA), distal metatarsal articular angle (DMAA), rotation type of the first metatarsal (RTFM), and the position of the tibial sesamoid (TSP). Results A total of 82 files were available for analysis. The mean age of the patients was 40.5 ± 13.8 (Median = 43) years; 67 (81,7%) were female, and 15 (18.3%) were male. The mean operation duration was 33.2 ± 3.0 min. The mean follow-up period was 22.7 ± 7.0 months. There was a linear relationship between the average age of the patients and the shortness (mm) values (r = 0.466; p < 0.001). The HVA, IMA, DMAA, TSP, and VAS scores were lower in the patients after the operation compared to before values (p < 0.001). The preoperative assessment of RTFM identified 15 cases with an angular type, 38 cases with an intermediate type, and 29 cases with a round type. The postoperative mean AOFAS value was higher than the mean score before the operation (p < 0.001). A dramatic reduction was observed in postoperative IMA and DMAA values (p < 0.001). Conclusion This study’s findings demonstrate the benefits of a new fixation method for treating HV that is applicable to all mild and moderate HV cases. This method enables intraoperative readjustment without compromising the fixation strength and has a short learning curve.